Human Polyomaviruses: The Battle of Large and Small Tumor Antigens. Issue 1 (29th November 2017) - Baez, Camila Freze; Brandão Varella, Rafael; Villani, Sonia; Delbue, Serena
About 40 years ago, the large and small tumor antigens (LT-Ag and sT-Ag) of the polyomavirus (PyVs) simian vacuolating virus 40 have been identified and characterized. To date, it is well known that all the discovered human PyVs (HPyVs) encode these 2 multifunctional and tumorigenic proteins, expressed at viral replication early stage. The 2 T-Ags are able to transform cells both in vitro and in vivo and seem to play a distinct role in the pathogenesis of some tumors in humans. In addition, they are involved in viral DNA replication, transcription, and virion assembly. This short review focuses on the structural and functional features of the HPyVs' LT-Ag and sT-Ag, with special attention to their transforming properties.